Necessary changes, adverse effects? The institutional patterns of adaptation of economics universities to changes prompted by the reform of Poland's science and higher education system. Issue 4 (September 2020) - Jelonek, Magdalena; Mazur, Stanisław
The currently implemented reform of Poland's science and higher education system extensively draws on the principles of new public management in both curricula and management. It also replicates, at times uncritically, the changes put into effect in European higher education institutions. As early as 2017, the intentions of the decision makers were made clear by the introduction of a new funding algorithm, which completely altered the existing rules of the game. This algorithm particularly affected public economics universities, which were forced to make some adaptations. In this article, we focus on ways in which economics universities adapted to two specific solutions proposed by the legislator, that is, (1) the new funding algorithm and (2) the new career path called 'teaching professorship'. Based on an in-depth study and using the theories of new institutionalism, we explore the mechanisms of adaptation to the new provisions as they apply to public economics universities. Finally, we identify and discuss four kinds of risks resulting directly from the new public management–based assumptions adopted by the reformers, namely, (1) the invasiveness of the proposed changes, (2) the fragmentary perception of the science and higher education system, (3) the inconsistency of the actions and (4) the ostensible adaptation measures taken by the institutions.